What lessons will the covid-19 leave us? History of the new coronaviruses - Pulcha-Ugarte, Renata (2020)
Coronaviruses have been present in humans for decades, causing 10-30% of common colds in humans. Two coronaviruses have caused global pandemics and alerts in recent decades: SARS- CoV and MERS-CoV. SARS-CoV-2 is the seventh coronavirus to generate an infection in humans, and the third to generate a pandemic. In this article, we present and compare the chronology, epidemiology, and control measures of each of thepandemics: SARS, MERS and COVID-19.